2014
DOI: 10.2337/db13-1686
|View full text |Cite
|
Sign up to set email alerts
|

Postexercise Improvement in Insulin-Stimulated Glucose Uptake Occurs Concomitant With Greater AS160 Phosphorylation in Muscle From Normal and Insulin-Resistant Rats

Abstract: Earlier research on rats with normal insulin sensitivity demonstrated that acute exercise increased insulin-stimulated glucose uptake (GU) concomitant with greater phosphorylation of Akt substrate of 160 kDa (pAS160). Because mechanisms for exercise effects on GU in insulin-resistant muscle are unknown, our primary objective was to assess insulin-stimulated GU, proximal insulin signaling (insulin receptor [IR] tyrosine phosphorylation, IR substrate 1–phosphatidylinositol-3-kinase, and Akt phosphorylation and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
140
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(166 citation statements)
references
References 50 publications
22
140
2
2
Order By: Relevance
“…Previous in vitro studies showed that 2 or 4 wk of HFD feeding impairs insulin-stimulated glucose uptake in skeletal muscle after endurance exercise in rats (18,19). We found that blood glucose levels at 120 min after exercise were significantly higher in the HFD group than in the Con group.…”
Section: Discussionsupporting
confidence: 43%
See 4 more Smart Citations
“…Previous in vitro studies showed that 2 or 4 wk of HFD feeding impairs insulin-stimulated glucose uptake in skeletal muscle after endurance exercise in rats (18,19). We found that blood glucose levels at 120 min after exercise were significantly higher in the HFD group than in the Con group.…”
Section: Discussionsupporting
confidence: 43%
“…Post-exercise glucose uptake in skeletal muscle is activated in an insulin-independent manner (contraction per se) and an insulin-dependent manner. A previous study showed that 2 wk of HFD intake did not affect the stimulation of glucose uptake in skeletal muscle induced by exercise with no insulin condition (19). Therefore, it is possible that pre-exercise HFD consumption for 3 d did not affect insulin-independent but only insulin-dependent glucose uptake during postexercise recovery.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations